Аналіз існуючих інформаційних систем громадських організацій - Іванова, С. І. (ХНУРЕ, 2024)
A comparative analysis of the use of information systems by volunteer organizations in different countries, as well as existing software applications in Ukraine, was conducted, and the results of the research will help Ukrainian volunteer organizations identify priority areas for the development and improvement of their work.
Keywords: Аналіз існуючих інформаційних систем громадських організацій; Аналіз існуючих інформаційних систем громадських організацій